Synergistic Effect of Honey Bee Venom and 1,25-Dihydroxyvitamin D3 on the Induction of HL-60 Promyelocytic Leukemia Cell Line Differentiation - Homa Mohseni Kouchesfehani; Kazem Parivar; Mohammad Nabiyouni; Maryam Rahimi (پزشکی بالینی ابن سینا, 2010)
Introduction & Objective: Acute promyelocytic leukemia (APL) is a kind of acute leukemia characterized by a balanced t (15, 17) translocation which fails to develop into mature cells and proliferate in an unregulated fashion. In the recent years, in addition to combinatoral chemotherapy to treat unmature cancerous cells, differentiation therapy by differentiating agents as a novel procedure are used. Since it is not possible to use high concentration of differentiating agents due to their side effects, some compounds are also used to increase their differentiating potency. In this study the effect of bee venom and 1,25-Dihydroxyvitamin D3 individually and in combination on proliferation and differentiation of HL-60 cancerous cells were assayed. Materials & Methods: In this experimental in vitro study , toxic and non-toxic concentrations of honey bee venom and 1,25- Dihydroxyvitamin D3 were determined using Trypan blue stained cell counting and MTT assay . In addition,differentiation of cells was assayed by Wright-Giemsa staining and NBT reduction test. Data were analized by one –way ANOVA test using SPSS software. Results: Our findings showed that both bee venom and 1,25-Dihydroxyvitamin D3 in a dose and time dependent manner caused cell death at high concentrations and inhibited cell proliferation at lower concentration. 1,25-Dihydroxyvitamin D3 at 5nM concentration induced differentiation of HL-60 cells towards monocyte during 72 hours. Bee venom at 2.5 µg/ml concentration suppressed proliferation of HL-60 cells but had not any effect on their differentiation , whereas in combination with 5nM 1,25-Dihydroxyvitamin D3 enhanced anti-proliferative and differentiation potency of 1,25-Dihydroxyvitamin D3.Conclusion: Non-toxic and inhibitory concentrations of bee venom can increase anti-proliferation and differentiation potency of 1,25-Dihydroxyvitamin D3.